Truncamento e reduplicação no português brasileiro (Revista de Estudos da Linguagem, 2002)
This paper investigates the morphology of truncation andreduplication processes in Brazilian Portuguese (BP). Truncation(also known as abbreviation) is the word formation process inwhich a word is shortened without loss any meaning. I argue thatthe BP’s truncated forms tend to be disyllabic and the secondarystress rhythm also plays a role in the process. The reduplicationinvolves copy of a piece or a complete word, promoting a newlexical item. There are several kinds of reduplication (cf. COUTO,1999), for the moment I will focus only on the total reduplicationverbi-verbi. I will show that both processes are regular andpredictable. Similarly, I will show the tendency of this wordformation to have an open final syllable and binary feet, offeringargument to the Emergence of the Unmarked Theory.